Cicatrices y tormentas: el pasado en cuestión. Memoria post-dictatorial en Nocturno de Chile de Bolaño y en crónicas de Lemebel - Vergini, Ludmila Sol (Confluenze. Rivista di Studi Iberoamericani, 2013)
Following Nelly Richard’s point of view about the closure of dictatorial past held out by the rhetoric of consensus in Chilean Transition to democracy, this paper examines two literary responses to this closure. On the one hand, Lemebel’s chronicles claim a place for collective memory of the silenced in public space. On the other hand, Bolaño’s novel, Nocturno de Chile, subverts the dictatorial official memory from within. In both cases, the interpretation of the past is problematized, contributing to keep memory alive.